(3QhGjI jhSa GdMSfs - (3YHO Gddg GdHSJGfjs
(3ChdgG (B:s
(3dGhi dbO Yjd ai PG GdbaQ eUWHQi hCKQJ ai aDGOi CSge GdVLQ s
(3BNQgG (B:s
(3jNQL aQYhf hGdhcjd jhSa ajgG HfG fONd CHj GdUMf efRdi dGcShce WQkG hGLHce JHQkG JeJ s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI s
Keywords: (3GdCOHs